Garçons manqués and femmes fortes: Two ambivalent figures of butch lesbianism in women's football in Cameroon - Ndjio, Basile (African Studies Review, 2022)
With the enactment of anti-homosexuality laws in the 1960s, Cameroon's government officially endorsed heterosexualist ideologies which legitimize the alienation and criminalization of minority and nonconforming sexual and gender identities. One group, the so-called garçons manqués, embodies the stigmatized masculine or "butch" lesbian identity. The political management of lesbianism in Cameroon is ambivalent, however, with respect to sport, and particularly regarding the national pastime, football. Whereas masculine lesbians are routinely branded as "butches" or "sexual predators" who threaten African hetero-patriarchy, "strong women"" (femmes fortes) are celebrated as pivotal to the national ambition. Cameroon's government strategically amalgamates both heteronationalism and homonationalism in the interest of national pride.
Keywords: afrique; anthropologie; approches et analyses; butch; cameroun; discipline; discours dominant; hétérosexisme; personnes lesbiennes; ressource en ligne; régions géographiques; sciences humaines; sexisme; sport; systèmes d'oppressions

Les femmes musulmanes et le « droit de choisir librement » - Abu-Lughod, Lila (Anthropologie et Sociétés, 2018)
Tout en soulignant qu’il s’avère illusoire de vouloir séparer les situations personnelles des conditions historiques et politiques de leur émergence, cet article propose une réflexion critique de la notion de libre choix, que l’auteure inscrit dans un réseau de facteurs macrosociaux tels que les tensions internationales ou encore la violence et la pauvreté structurelles. La notion de « libre choix » possède une charge idéologique qui se reflète dans la distinction souvent établie entre les femmes occidentales libérées et la femme musulmane dépourvue de libre choix et victime passive de l’oppression patriarcale. Le libre choix tend aujourd’hui à (re)devenir un critère discriminatoire permettant de distinguer les sociétés les « plus civilisées » (choix et liberté pour les « Occidentales ») de celles qui le sont moins (contrainte et servitude pour les « Orientales »). La violation du libre choix des femmes peut alors contribuer à légitimer l’intervention des industries humanitaire et militaire pour « sauver les musulmanes », comme cela a été le cas dans la guerre d’Afghanistan, à la suite des événements tragiques du 11 septembre 2001. Qui a le pouvoir de réduire « l’Autre », et particulièrement les musulmanes, à des sujets assujettis incapables d’émerger comme sujets agissants ? Des musulmanes souffrent d’un libre choix limité, mais ceci est-il réductible à l’islam ? Le libre choix des Occidentales relève-t-il d’un idéal fantasmé ? Faudrait-il plutôt investiguer la notion de libre choix dans sa complexité intrinsèque reliée aux relations de pouvoir ? Réduire les vies poignantes et tellement complexes des femmes musulmanes à une question de choix plus ou moins libre et éclairé est d’une totale insatisfaction pour l’anthropologue. Afin de mieux saisir cette complexité, l’auteure puise dans son travail ethnographique s’échelonnant sur une vingtaine d’années en milieu rural égyptien pour souligner l’importance du travail (micro)ethnographique qui permet de dépasser les généralités et les simplicités galvaudées par certains médias et romans à sensation (« pulp nonfiction ») qui font et défont l’opinion publique. L’auteure compare ces généralités essentialisantes avec des exemples de vies socialement complexes et ethnographiquement riches de villageoises égyptiennes.
disponible en ligne à http://dx.doi.org/10.7202/1045123ar Donné en lecture dans le cours pol4212.
Keywords: afrique; anthropologie; approches et analyses; corps; cours; discipline; féminisme décolonial; féminisme islamique; pol4212; premier cycle; racisme; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; égypte

Geographies of privilege - Twine, France Winddance; Gardener, Bradley (Routledge, 2013)
How are social inequalities experienced, reproduced and challenged in local, global and transnational spaces? What role does the control of space play in distribution of crucial resources and forms of capital (housing, education, pleasure, leisure, social relationships)? The case studies in Geographies of Privilege demonstrate how power operates and is activated within local, national, and global networks. Twine and Gardener have put together a collection that analyzes how the centrality of spaces (domestic, institutional, leisure, educational) are central to the production, maintenance and transformation of inequalities. The collected readings show how power–in the form of economic, social, symbolic, and cultural capital–is employed and experienced. The volume's contributors take the reader to diverse sites, including brothels, blues clubs, dance clubs, elite schools, detention centers, advocacy organizations, and public sidewalks in Canada, Italy, Spain, United Arab Emirates, Mozambique, South Africa, and the United States. Geographies of Privilege is the perfect teaching tool for courses on social problems, race, class and gender in Geography, Sociology and Anthropology.
Keywords: afrique; afrique du sud; amériques; anthropologie; approches et analyses; canada; classe sociale; discipline; environnement; espagne; europe; géographie; italie; mozambique; outils; ouvrages de références; privilèges; racisme; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; émirats arabes unis; états-unis

Lost boys, invisible girls: stories of Sudanese marriages across borders - Grabska, Katarzyna (Gender, Place & Culture, 2010)
Forced migration challenges and changes gender relations. The transnational activities of refugees resettled in the West create gender asymmetries among those who stay behind. This article explores the transnational marriages of young southern Sudanese women (‘invisible girls’), who either stayed in Sudan or remained in refugee camps in Kenya, to Sudanese men who were resettled to America, Canada or Australia (‘lost boys’). Incorporating gender as a relational category into the analysis of transnational practices that migrants and refugees engage in is important. The article argues that there is a need to put feminist analysis at the centre of transnational processes resulting from (forced) migration. It looks at the connections between different geographical locations, the impacts of the migration of young refugee men on bridewealth and marriage negotiations and the gender consequences for young women, men and their families. It is argued that transnational activities, such as marriage, contest, reconfigure and reinforce the culturally inscribed gender norms and practices in and across places. Transnational marriage results in ambiguous benefits for women (and men) in accessing greater freedoms. Anthropological analyses of marriage need a geographical focus on the transnational fields in which they occur. The article seeks to deepen understanding of the nuanced gendered consequences of transnationalism. It shows how gender analysis of actions taken across different locations can contribute to the theorisation of transnational studies of refugees and migrants.
Keywords: 2000 à aujourd'hui; 2000-2009; afrique; amériques; anthropologie; anthropologie sociale; approches et analyses; australie; canada; cours; discipline; histoire et politique; kenya; mariage; migration; océanie; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexisme; soudan; systèmes d'oppressions; thématiques; transnationalisme; états-unis

Les clôtures symboliques des Algériennes: la virginité ou l'honneur social en question - FERHATI, Barkahoum (Clio. Femmes, Genre, Histoire, 2007)
Liée à l'honneur de la famille, la virginité est une question qui a toujours hanté l'esprit des jeunes filles algériennes. Toutes sortes de pratiques sont envisagées par la société pour la préserver. La plus connue est celles du rbat (action de nouer), dit teskar (action de fermer) ou encore tesfah (action de blinder). Au moyen de techniques ritualisées, elle consiste en la « fermeture » symbolique de l'hymen avant la puberté et son « ouverture » symbolique la veille du mariage. La « chemise tachée du sang de la vierge » doit en être la preuve indéniable: elle authentifie que l'honneur de la famille, du groupe, est intact. Lorsque, pour diverses raisons, l'hymen fait défaut, la société déploie toutes sortes de stratégies palliatives. Aujourd'hui, le certificat de virginité et la reconstitution de l'hymen par la chirurgie plastique, l'hyménorrapie ou l'hyménoplastie, viennent renforcer la pratique symbolique du rabt. La question fondamentale que je pose dans cet article est: peut-on envisager de casser la clôture « malléable » de cette « vaste prison » des femmes afin que les Algériennes puissent intégrer la société en tant qu'individus et non en tant qu'emblèmes de l'honneur de la famille?
Keywords: afrique; algérie; anthropologie; approches et analyses; corps; cours; discipline; féminisme islamique; histoire; hymen; patriarcat; premier cycle; rapports sociaux de sexe; ressource en ligne; rituel; régions géographiques; sciences humaines; sex2283; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; virginité

Transcultural bodies: female genital cutting in global context - Hernlund, Ylva; Shell-Duncan, Bettina (Rutgers University Press, 2007)
Female "circumcision" or, more precisely, female genital cutting (FGC), remains an important cultural practice in many African countries, often serving as a coming-of-age ritual. It is also a practice that has generated international dispute and continues to be at the center of debates over women's rights, the limits of cultural pluralism, the balance of power between local cultures, international human rights, and feminist activism. In our increasingly globalized world, these practices have also begun immigrating to other nations, where transnational complexities vex debates about how to resolve the issue. Bringing together thirteen essays,Transcultural Bodiesprovides an ethnographically rich exploration of FGC among African diasporas in the United Kingdom, Europe, and Australia. Contributors analyze changes in ideologies of gender and sexuality in immigrant communities, the frequent marginalization of African women's voices in debates over FGC, and controversies over legislation restricting the practice in immigrant populations.
Keywords: afrique; anthropologie; approches et analyses; australie; corps; cours; discipline; europe; histoire et politique; océanie; premier cycle; racisme; ressource en ligne; royaume-uni; régions géographiques; santé; sciences humaines; sex2283; sexisme; sexualité; sociologie; système colonial; systèmes d'oppressions; thématiques; transculturalisme; violences

The female circumcision controversy: an anthropological perspective - Gruenbaum, Ellen (University of Pennsylvania Press, 2001)
To the Western eye, there is something jarringly incongruous, even shocking, about the image of a six-year-old girl being held down by loving relatives so that her genitals can be cut. Yet two million girls experience this each year. Most Westerners, upon learning of the practice of female circumcision, have responded with outrage; those committed to improving the status of women have gone beyond outrage to action by creating various programs for "eradicating" the practice. But few understand the real life complexities families face in deciding whether to follow the traditional practices or to take the risk of change. InThe Female Circumcision Controversy, Ellen Gruenbaum points out that Western outrage and Western efforts to stop genital mutilation often provoke a strong backlash from people in the countries where the practice is common. She looks at the validity of Western arguments against the practice. In doing so, she explores both outsider and insider perspectives on female circumcision, concentrating particularly on the complex attitudes of the individuals and groups who practice it and on indigenous efforts to end it. Gruenbaum finds that the criticisms of outsiders are frequently simplistic and fail to appreciate the diversity of cultural contexts, the complex meanings, and the conflicting responses to change. Drawing on over five years of fieldwork in Sudan, where the most severe forms of genital surgery are common, Gruenbaum shows that the practices of female circumcision are deeply embedded in Sudanese cultural traditions-in religious, moral, and aesthetic values, and in ideas about class, ethnicity, and gender. Her research illuminates both the resistance to and the acceptance of change. She shows that change is occurring as the result of economic and social developments, the influences of Islamic activists, the work of Sudanese health educators, and the efforts of educated African women. That does not mean that there is no role for outsiders, Gruenbaum asserts, and she offers suggestions for those who wish to help facilitate change. By presenting specific cultural contexts and human experiences with a deep knowledge of the tremendous variation of the practice and meaning of female circumcision, Gruenbaum provides an insightful analysis of the process of changing this complex, highly debated practice.
Section: 242 p. ; 23 cm
Keywords: afrique; anthropologie; approches et analyses; corps; cours; discipline; histoire et politique; justice sociale; point de vue situé; premier cycle; ressource en ligne; régions géographiques; santé; sciences humaines; sex2283; soudan; système colonial; systèmes d'oppressions; thématiques; violences